LITERASI INVESTASI BAGI GENERASI Z PADA SMK KARYA PEMBANGUNAN DI KABUPATEN TANGERANG - Atmaja, Sena; Perwitahasari, Resy; Naim, Abu; Hadi, Helmas Septiyo; Dadang, Dadang; Rosidawaty, Rosidawaty; Wangsih, Ingkak Chintya; Ambarwati, Rina; Gumilang, Andika Mugi; Aminudin, Dindin; Sugiyono, Sugiyono; Ulinuha, Nor Fattah; Faroqi, Fachmi Al; Maesaroh, Siti (Jurnal Abdi Insani, 2025)
The Faculty of Economics and Business at Muhammadiyah University A.R. Fachruddin is implementing a community service program with the theme "Investment Literacy for Generation Z" at SMK Karya Pembangunan. The purpose of this activity is to raise students' awareness and understanding of the importance of investing from an early age, especially for Generation Z, who are preparing for their financial future. This program covers a variety of materials on the basics of investing, different types of investments, risks and returns, and appropriate investment strategies. This program uses seminars, workshops, and investment simulations to provide students with practical experience. All these methods are designed to give students the opportunity to directly experience the dynamics of the investment world by actively engaging them in discussions and simulation activities. Additionally, this program involves several investment practitioners as resource persons, who provide insights and knowledge from their own experiences. The pre-test and post-test results show a significant improvement in students' understanding of investment. With this program, it is hoped that students of SMK Karya Pembangunan will have sufficient knowledge to manage their finances and make wise investment decisions in the future.